Komitmen Organisasional Karyawan Indomaret Di Bojonegoro ditinjau dari Keadilan Organisasional, Kepuasan Kerja dan Trust - Sri Umayatin; Tri Siwi Agustina (Faculty of Economics and Business University of Lampung, 2023)
Organizational Commitment is an important issue for a company to improve. The level of Organizational Commitment can affect how much employees intend to stay in the organization. This study aims to examine the effect of justice felt by employees (organizational justice) and job satisfaction in the organization which will have an impact on the desire to survive in the organization (Organizational Commitment). This study also analyzes Trust as a moderating variable. This study uses a quantitative approach with a survey method, using primary data from 79 employees where data is obtained using a questionnaire distributed to employees of PT. Indomarco Prismatama (Indomaret) in Bojonegoro. The sampling procedure was carried out by purposive sampling method, on employees of Indomaret in Bojonegoro area and positions not as store heads. The research uses Smart PLS 3.0 software to facilitate data analysis techniques. The results of this study show that organizational justice has a positive and significant effect on Organizational Commitment, job satisfaction has a significant positive effect on Organizational Commitment. Trust as moderation does not moderate the effect of organizational fairness on organizational commitment, nor does trust moderate the effect of job satisfaction on organizational commitment